LEGAL RESPONSIBILITY FOR UNLAWFUL ACTS IN THE SALE AND PURCHASE OF LAND BY PPAT (CASE STUDY OF DECISION NUMBER 40/PDT.G/2015/PN KLN AND DECISION NUMBER 555/PDT/2015/PT SMG) - ELMYLIANTIKA MARANANTA (Authentica, 2023)
In making authentic deeds, PPAT often improperly carry out its obligations in accordance to an applicable regulation or the ethic code binds it. The non-compliance when carrying out the obligations causes the PPAT position losses to one of the parties involved, which can be considered an unlawful act. As a result, the deed becomes void, invalid and legally defective. This research discusses the issue of Legal Responsibility for Unlawful Actions in the Case of Buying and Selling Land by PPAT (Case Study of Decision Number 40/PDT.G/2015/PN KLN and decision Number 555/Pdt/2015/PT SMG). The research method in this research is normative juridical research using secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The research results of this research are that if the agreement is proven to be null and void, the deed of sale and purchase agreement made by PPAT to prove a transaction is legally flawed and has no legal force, as a result, the title certificate having no legal force. Regarding the responsibility of the PPAT which makes the Deed of Sale and Purchase resulting in losses for one of the parties therein, they can be held civilly liable with compensation for the unlawful acts they have committed, administrative liability, namely resigning as a public official or being dishonorably dismissed by the competent Ministry due to a fatal act and tarnished the good name of the notary association and the PPAT association, as well as criminal liability for violating Article 263 of the Criminal Code concerning forgery which can be subject to imprisonment.Keywords: Responsibility; PPAT; Unlawful Acts; Buying and Selling Land.